2019
DOI: 10.3389/fneur.2019.01138
|View full text |Cite
|
Sign up to set email alerts
|

SCN4A p.R675Q Mutation Leading to Normokalemic Periodic Paralysis: A Family Report and Literature Review

Abstract: Objective: To investigate the clinical features, skeletal muscle imaging, and muscle pathological characteristics of normokalemic periodic paralysis (NormoKPP) caused by mutation of SCN4A gene p.R675Q.Methods: The clinical data, skeletal muscle imaging, pathological data, and gene test results of a family with NormoKPP were collected in detail in October 2018. The previous literature was reviewed and used for comparative analysis.Results: The proband was a 28-year-old male with paroxysmal weakness of both lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…If present, muscle biopsies to specifically look for core pathology should be considered. Structural pathology consistent with cores in our opinion (originally reported as target lesions) has been reported in one kindred with normokalaemic PP, which is believed to be within the spectrum of HyperPP 52,53 . However, they have not been a common finding in PP.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…If present, muscle biopsies to specifically look for core pathology should be considered. Structural pathology consistent with cores in our opinion (originally reported as target lesions) has been reported in one kindred with normokalaemic PP, which is believed to be within the spectrum of HyperPP 52,53 . However, they have not been a common finding in PP.…”
Section: Resultssupporting
confidence: 78%
“…However, they have not been a common finding in PP. In this case, the gastrocnemius was biopsied, and the biopsy was taken after a very prolonged attack after which the patient had not fully recovered force 53 . Gastrocnemius is one of the most commonly and severely affected muscles on MRI of HyperPP patients 54 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The depolarization of sarcolemma leads to inactivation of Na V 1.4 channels to cause periodic paralysis [29,30]. It has been reported that R675Q mutation can cause HypoPP2 in Chinese patients [6], but this mutation is more common in NormoPP [8,9] and can also be seen in HyperPP [31]. T704M mutation in the S5 segment of domain II can result in impaired fast or slow inactivation of Na V 1.4 channel, and, therefore, persistent increased sodium current and sarcolemmal depolarization, which can result in the symptom of paralysis [32,33].…”
Section: Geneticsmentioning
confidence: 99%